A Regional Edge Cluster Approach for Reliable Connectivity in Mobile Healthcare IoT Systems - Ali AL-ALLAWEE; Senan A. M. Alhasan (Politeknik Ganesha Medan, 2026)
Healthcare applications are known to be critical and time-sensitive nowadays. Recently, several healthcare applications have been deployed utilizing Internet of Things (IoT) technology due to its capability of management, efficiency of treatments and mobility which yield accordingly to improve patients’ health. Successful stories have been achieved between IoT-healthcare and Edge computing to support smooth mobility and near processing. However, patient mobility, especially with high speed transportation and intersection, leads IoT-healthcare devices to loss connections and/or process with latency. This paper proposes a Patient Mobility Control under Edge Computing (PMC-EC) mechanism that aims to guaranty and enhance the connectivity between patients (IoT Health sensors) and cloud by using edge computing paradigm in the middle. The objectives are achieved by utilizing cluster management strategies which arranged between cloud and edge computing servers. The mechanism is implemented in OpenStack cloud servers and evaluated by calculating the latency and throughput parameters in two different scenarios. The results, in sum, are collected with promised indication of latency and throughput values to provide acceptable performance.